South Atlantic continental margins of Africa: a comparison of the tectonic vs climate interplay on the evolution of equatorial west Africa and SW Africa margins - (:unkn) unknown (My University, 2005)
The comparative review of 2 representative segments of Africa continental margin: the equatorial western Africa and the SW Africa margins, helps in analysing the main controlling factors on their development. Early Cretaceous active rifting S of the Walvis Ridge resulted in the formation of the SW Africa volcanic margin. The non-volcanic rifting N of the Walvis ridge, led to the formation of the equatorial western Africa margin, with thick and extensive, synrift basins. Regressive erosion of SW Africa prominent shoulder uplift accounts for high clastic sedimentation rate in Late Cretaceous - Eocene, while dominant carbonate production on equatorial western Africa shelf suggests little erosion of a low hinterland. The early Oligocene climate change had contrasted response in both margins. Emplacement of the Congo deep-sea fan reflects increased erosion in equatorial Africa, under the influence of wet climate, whereas establishment of an arid climate over SW Africa induced a drastic decrease of denudation, and thus reduced sedimentation on the margin. Neogene emplacement of the African superswell beneath S. Africa renewed onshore uplift on both margins, but it accelerated erosion only in the Congo catchment, due to wetter climate. Neogene high sedimentation rate reactivated gravitational tectonics that had remained quiescent since late Cretaceous.
Keywords: African Research